Mixed-matrix membranes of zeolitic imidazolate framework (ZIF-8)/Matrimid nanocomposite: Thermo-mechanical stability and viscoelasticity underpinning membrane separation performance - Mahdi, E; Tan, J (Elsevier, 2015)
Mixed-matrix membranes (MMMs) containing nanoporous metal-organic frameworks (MOFs) represent a rapidly expanding class of next-generation membranes, targeting CO2 capture, gas purification, and novel electrochemical technologies. In this work, we have performed an in-depth study to elucidate the basic mechanical properties underpinning the functional performance of the prototypical ZIF-8/Matrimid® nanocomposite membranes. By adopting the colloidal solution mixing method, we have fabricated membranes with 0–30 wt% ZIF-8 nanoparticles, whose quasi-static, temperature- and time-dependent mechanical characteristics have been established by means of nanoindentation, dynamic mechanical analysis, and large-strain uniaxial tensile measurements. We show that the inclusion of ZIF-8 nanoparticles into Matrimid (a glassy polyimide) controls many important mechanical behaviour, ranging from elastic modulus, yield strength and hardness, to ductility (stretchability), fracture strength and toughness. We identified that annealing (180 °C), despite improving the gas permeability and selectivity of Matrimid-based membranes, could substantially degrade its ductility and fracture toughness, while stabilising small-strain viscoelastic response under dynamic loading. Our results suggest that an annealed <~10 wt% ZIF-8/Matrimid MMM would be ideal for practical separation applications, where an optimal combination of mechanical resilience in conjunction with excellent gas permselectivity are the prerequisites.